Case report: Demodicosis in a Chow-chow dog at Yours Veterinary Clinic in Padang Panjang City - Ridho Gelagar, Ario; Sukmawati, Yofa; Ramadhan, Juliadi; Aulia, Usma; Zukiaturrahmah, Anna (Future Science, 2023)
Demodecosis, also known as Red Mange, Acarus Mange, and Follicular Mange, is a skin disease caused by the mite Demodex canis. Demodecosis infection can occur in dogs of all ages. This study aims to diagnose and treat the infection of Demodex sp in chow-chow dogs. Clinical signs include generalized alopecia, scales, and crusts found on the body's surface, followed by dehydration symptoms, poor skin turgor, and long CRT. Supporting examinations to determine demodecosis infection are carried out using the deep skin scrapping test method. Next, a hematological exam was carried out. The hematology examination interpreted the blood analysis results to indicate that the dog had normochromic microcytic anemia. A decrease in RBC, hemoglobin, and hematocrit indicates anemia. A low MCV indicates Microcytic, and normochromic is due to a normal MCHC. Treatment is carried out by administering ivermectin, diphenhydramine HCl, and longamox.